Ranibizumab for the treatment of choroidal neovascularization due to cause other than age related macular degeneration - Stepanov, A; Středová, M; Dusová, J; Jirásková, N; Studnička, J (Ceska a slovenska oftalmologie, 2019)
PURPOSE: To evaluate the safety and clinical efficacy of ranibizumab (Lucentis) in the treatment of choroidal neovascularization (CNV) caused by diseases other than age-related macular degeneration (AMD). PATIENTS: 21 patients with mean age 61  17.2 years (min 16, max 85) with CNV due to causes other than AMD, in particular pathological myopia (n=11), angioid streaks (n=3), central serous chorioretinopathy (n=2), North Carolina macular dystrophy (n=1), dominant familial drusen (n=1) and idiopathic CNV (n=3). METHODS: The patients were treated at the Ophthalmology Department of the University Hospital in Hradec Kralove with three monthly initial intravitreal injections of ranibizumab 0.5 mg with subsequent treatment regimen pro re nata (PRN). The best corrected visual acuity (BCVA) was evaluated on the ETDRS optotypes (Early Treatment Diabetic Retinopathy Study), central retinal thickness (CRT) was measured by optical coherent tomography (OCT) (Zeiss, Cirrus). These parameters were evaluated before start of the study and then at 1 (BCVA only), 4, 8, and 12 months during treatment. We also evaluated the possible occurrence of ocular and systemic side effects. RESULTS: Statistically significant improvement in the mean of BCVA score of 11.4 letters (p.
Keywords: dospělí; Tomography, Optical Coherence; injekce intravitreální; myopic CNV; Lucentis; neovaskularizace choroidey; Adult; výsledek terapie; mladý dospělý; Adolescent; optická koherentní tomografie; lidé; Angiogenesis Inhibitors; inhibitory angiogeneze; Treatment Outcome; Aged, 80 and over; other cause than AMD; Intravitreal Injections; Choroidal Neovascularization; Aged; anti-VEGF; Young Adult; ranibizumab; lidé středního věku; humanizované monoklonální protilátky; senioři nad 80 let; senioři; Antibodies, Monoclonal, Humanized; zraková ostrost; Ranibizumab; Visual Acuity; Middle Aged; mladiství; Humans